Socioeconomic, demographic and obstetric determinants of maternal near miss in Africa: A systematic review - Mory Diakite; Vincent de Brouwere; Bouchra Assarag; Zakaria Belrhiti; Saad Zbiri; Mohamed Khalis (PLoS ONE, 2025)
Background High rates of maternal mortality and morbidity remain significant health issues in low- and middle-income countries. Despite this, few researchers have investigated the underlying factors of severe maternal complications in sub-Saharan Africa. Therefore, the objective of this systematic review was to determine the socioeconomic, demographic, and obstetric predictors of severe maternal complications in this region. Method For this systematic review, we searched PubMed, Scopus and Science Direct between 2000 and 2022. Studies were eligible if they reported a relationship between impending maternal death and one or more socioeconomic, demographic or obstetric determinants. We did not contact the authors of the articles, as we had access to their full texts. The quality of qualitative and quantitative studies was assessed using the Critical Appraisal Skills quality assessment tool. Results Among the 3001 identified studies, this systematic review selected 25 articles. Factors such as economic status, level of education, maternal age, marital status, rural residence, transfers to other facilities, and delays during childbirth were identified as the main determinants of severe complications occurrence in Africa. Disparities in access to maternal healthcare were observed among women from different socioeconomic groups, often due to power imbalances in decision-making processes. Conclusion Several factors, including education, prenatal care follow-up, pre-existing medical conditions, method of admission, and mode of delivery, have been identified as significant indicators of the likelihood of severe maternal morbidity. To reduce these cases, it is crucial to implement targeted socio-economic development programs, including improving access to education, strengthening prenatal health services, providing support to pregnant women with pre-existing medical conditions, and ensuring appropriate admission and delivery methods.